O ensino do brinquedo/brinquedo terapêutico nos cursos de graduação em enfermagem no Estado de São Paulo - Cintra, Sílvia Maira Pereira [UNIFESP] (2006)
This study is a descriptive and quantitative research that aims to characterize the toy / therapeutic toy teaching and analyze the facilities and difficulties of its development in the graduation courses in nursing in São Paulo State. The data was collected in 40 institutions, where there were 76 participant professors. The results showed that the theme is approached in the programmatic content of Pediatric Nursing in most of these institutions, in the third, more effectively in the last ten years, both in the theoretical and practical teaching. The theoretical load time had a variation of one to 20 hours, using expositive and participative class and the written test prevailed in the theoretical evaluation strategies and in the practical, the students observation. Some difficulties and facilities mentioned refer to valorization and to infra structure favorable to these resources.